Assessment of risk factors for cerebrovascular disease among the elderly in Beijing: A 23-year community-based prospective study in China. (November 2018) - Li, Haibin; Guo, Jin; Wang, Anxin; Zhang, Deqiang; Luo, Yanxia; Wang, Wei; Li, Xia; Tang, Zhe; Guo, Xiuhua
Highlights: Males are at higher risk of cerebrovascular diseases (CBVD) than females. Hypertension, cognitive impairment and depression are vital risk factors of CBVD. A simple risk screen scale for CBVD was built among Chinese older adults. Abstract: Introduction: There are few studies on how lifestyle factors and mental conditions modulate the cerebrovascular diseases (CBVD) mortality risk are rare in the Asian elderly. Aim: To comprehensively assess the impact of lifestyle factors and mental conditions on the mortality risk of CBVD among the Chinese older adults. Material and methods: This community-based prospective cohort study was based on the Beijing Longitudinal Study of Aging. We included 2101 participants aged ≥55 years who were interviewed in August 1992 and followed until December 2015. Baseline sociodemographic variables, lifestyle behaviors, and medical conditions were collected using a standard questionnaire. In addition, biochemical parameters, the Activities of Daily Living (ADL) scale, Center for Epidemiological Studies Depression (CES-D) scale, and Mini-Mental State Examination (MMSE) were performed. Hazard ratio (HR) and 95% confidence intervals (CI) was estimated from the competing risk model. Results: During the follow-up period, 576 (27.42%) CBVD events were documented. Multivariable analysis showed that hypertension (HR = 2.331, 95% CI = 1.652–3.288, P < 0.001), depression (HR=2.331, 95% CI=1.652-3.288, P < 0.001), cognitive impairment (HR=1.382, 95% CI=1.132-1.689, P < 0.001), and coronary heart diseases (HR=1.360, 95% CI=1.095-1.689, P = 0.005) were independently associated with CBVD, while body mass index, fasting blood glucose, triglycerides, drinking, and smoking were not associated with CBVD (all P > 0.05). Conclusions: Males were at higher risk of CBVD than females. Age, gender, hypertension, cognitive impairment, and depression were associated with CBVD among the elderly in Beijing, China.